Key role for EphB2 receptor in kidney fibrosis. Issue 17 (17th September 2021) - Huang, Zhimin; Liu, Simeng; Tang, Anna; Al-Rabadi, Laith; Henkemeyer, Mark; Mimche, Patrice N.; Huang, Yufeng
Abstract: Erythropoietin producing hepatocellular (Eph)–Eph receptor interacting (Ephrin) receptor–ligand signaling has been implicated in the development of tissue fibrosis, though it has not been well defined in the kidney. We detected substantial up-regulation of expression and phosphorylation of the EphB2 receptor tyrosine kinase in fibrotic kidney tissue obtained both from mice subjected to the unilateral renal ischemia–reperfusion (IR) model at 14 days and in patients suffering from chronic kidney disease (CKD). Knockout (KO) mice lacking EphB2 expression exhibited a normal renal structure and function, indicating no major role for this receptor in kidney development or action. Although IR injury is well-known to cause tissue damage, fibrosis, and renal dysfunction, we found that kidneys from EphB2 KO mice showed much less renal tubular injury and retained a more preserved renal function. IR-injured kidneys from EphB2 KOs exhibited greatly reduced fibrosis and inflammation compared with injured wildtype (WT) littermates, and this correlated with a significant reduction in renal expression of profibrotic molecules, inflammatory cytokines, NADPH oxidases, and markers for cell proliferation, tubular epithelial-to-mesenchymal transition (EMT), myofibroblast activation, and apoptosis. A panel of 760 fibrosis-associated genes were further assessed, revealing that 506 genes in WT mouse kidney following IR injury changed their expression. However, 70.9% of those genes were back to or close to normal in expression when EphB2 was deleted. These data indicate that endogenous EphB2 expression and signaling are abnormally activated after kidney injury and subsequently contribute to the development of renal fibrosis via regulation of multiple profibrotic pathways.